Quercetin-Crosslinked Chitosan Films for Controlled Release of Antimicrobial Drugs - Wiggers, Helton José; Chevallier, Pascale; Copes, Francesco; Simch, Fernanda Heloisa; da Silva Veloso, Felipe; Genevro, Giovana Maria; Mantovani, Diego (Frontiers in Bioengineering and Biotechnology, 2022)
Natural polymer-based films, due to their favourable biological and mechanical properties, have demonstrated great potential as coatings for biomedical applications. Among them, chitosan films have been widely studied both as coating materials and as drug-controlled release systems. Crosslinkers are often used to tune chitosan crosslink degree and thus to control the drug release kinetics. For this purpose, quercetin, a plant-derived natural polyphenol, has gained attention as a crosslinker, mainly for its intrinsic anti-inflammatory, antioxidant and anti-bacterial features. In this study, chitosan films crosslinked with three different concentrations of quercetin (10, 20, and 30 % w/w) have been produced as controlled release systems for the delivery of the antibacterial drug trimethoprim (TMP, 10 % w/w). Physicochemical and antimicrobial properties were investigated. Surface wettability and composition of the films were assessed by contact angle measurements, X-ray Photoelectron Spectroscopy (XPS), and Fourier-Transform Infrared spectroscopy (FTIR), respectively. The release kinetic of TMP in phosphate buffer saline (PBS) and 2-(N-morpholino) ethanesulfonic acid (MES) was studied over time. Finally, antibacterial properties were assessed on E. coli and S. aureus through Kirby-Bauer disc diffusion and micro-dilution broth assays. Results show that quercetin, at the tested concentrations, clearly increases the crosslinking degree in a dose-dependent way, thus influencing the release kinetic of the loaded TMP, while maintaining its bactericidal effects. In conclusion, this work demonstrates that quercetin-crosslinked chitosan films represent a promising strategy for the design of antibiotic-releasing coatings for biomedical applications.